Crustal structure of the Bighorn Mountains region: Precambrian influence on Laramide shortening and uplift in north‐central Wyoming. Issue 1 (30th January 2016) - Worthington, Lindsay L.; Miller, Kate C.; Erslev, Eric A.; Anderson, Megan L.; Chamberlain, Kevin R.; Sheehan, Anne F.; Yeck, William L.; Harder, Steven H.; Siddoway, Christine S.
Abstract: The crustal structure of north‐central Wyoming records a history of complex lithospheric evolution from Precambrian accretion to Cretaceous‐Paleogene Laramide shortening. We present two active source P wave velocity model profiles collected as part of the Bighorn Arch Seismic Experiment in 2010. Analyses of these velocity models and single‐fold reflection data, together with potential field modeling of regional gravity and magnetic signals, constrain crustal structure and thickness of the Bighorn region. We image a west dipping reflection boundary and model a sharp magnetic contact east of the Bighorn Arch that together may delineate a previously undetected Precambrian suture zone. Localized patches of a high‐velocity, high‐density lower crustal layer (the "7.× layer") occur across the study area but are largely absent beneath the Bighorn Arch culmination. Moho topography is relatively smooth with no large‐scale offsets, with depths ranging from 50 to 37 km, and is largely decoupled from Laramide basement topography. These observations suggest that (1) the edge of the Archean Wyoming craton lies just east of the Bighorn Mountains, approximately 300 km west of previous interpretations, and (2) Laramide deformation localized in an area with thin or absent 7.× layer, due to its relatively weak lower crust, leading to detachment faulting. Our findings show that Precambrian tectonics in northern Wyoming may be more complicated than previously determined and subsequent Laramide deformation may have been critically dependent on laterally heterogeneous crustal structure that can be linked to Precambrian origins. Key Points: P wave tomography constrains crustal structure of the WY Bighorn Mountains region Heterogeneous crustal structure linked to Precambrian processes Laramide Bighorn Arch collocated with inherited Precambrian structures